2013
DOI: 10.1111/tri.12169
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of a prospective, randomized trial comparing two machine perfusion devices used for kidney preservation

Abstract: SummaryStudies have shown beneficial effects of machine perfusion (MP) on early kidney function and long-term graft survival. The aim of this study was to investigate whether the type of perfusion device could affect outcome of transplantation of deceased donor kidneys. A total of 50 kidneys retrieved from 25 donors were randomized to machine perfusion using a flow-driven (FD) device (RM3; Waters Medical Inc) or a pressure-driven (PD) device (LifePort; Organ Recovery Systems), 24 of these kidneys (n = 12 pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although leaps forward in machine perfusion 3341,6567 , organ cryopreservation 26,27,68 , understanding scientific mechanisms of ischemic injury and metabolic regulation 2932,41 , and other areas have created a blueprint for transforming organ preservation, today maximum clinical organ preservation times are measured in hours, varying according to the organ transplanted, and necessitate transplantation almost immediately after the organ is recovered (http://www.nedonation.org/donation-guide/organ/acceptable-ischemic-times). Organs are rushed to their destinations, often by jet, or by helicopter flight straight to a landing pad on the transplant center rooftop.…”
Section: The Unrealized Potential Of Organ Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although leaps forward in machine perfusion 3341,6567 , organ cryopreservation 26,27,68 , understanding scientific mechanisms of ischemic injury and metabolic regulation 2932,41 , and other areas have created a blueprint for transforming organ preservation, today maximum clinical organ preservation times are measured in hours, varying according to the organ transplanted, and necessitate transplantation almost immediately after the organ is recovered (http://www.nedonation.org/donation-guide/organ/acceptable-ischemic-times). Organs are rushed to their destinations, often by jet, or by helicopter flight straight to a landing pad on the transplant center rooftop.…”
Section: The Unrealized Potential Of Organ Transplantationmentioning
confidence: 99%
“…This creates exciting prospects for translating the ‘suspended animation’ programs of animals, such as the arctic ground squirrel 153 and even tardigrade 154 , into tools for organ and tissue preservation. This decade has also seen rapid advances in ex vivo perfusion platforms 33,34,3638,41,66 , which can be adapted to recapitulate aspects of an organ’s in vivo environment, condition it for storage or transport in a hypometabolic state, or enhance recovery from stresses experienced during donor death or the preservation period 40,155158 . By building on, and combining, these innovations from different disciplines, we are now poised to create a new generation of organ and tissue preservation capabilities driven by both public and private sector funding (Box 1).…”
Section: An Integrated Approach To Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…HOPE was performed for 1 hour through the renal artery (aortic patch) with a constant perfusion pressure of <18 mm Hg, 20 and active oxygenation ( pO 2 60 to 80 kPa). We used 50 mL recirculating Kidney-Perfusion Solution-1 (KPS-1) as perfusate.…”
Section: Hypothermic Oxygenated Perfusionmentioning
confidence: 99%
“…When comparing standard static cold storage in kidneys vs. use of HMP for preservation, studies have shown the HMP group kidneys to have a lower incidence of delayed graft function, although there remains controversy regarding long-term graft survival and patient survival rates [39][40][41][42][43][44]. When comparing standard static cold storage in kidneys vs. use of HMP for preservation, studies have shown the HMP group kidneys to have a lower incidence of delayed graft function, although there remains controversy regarding long-term graft survival and patient survival rates [39][40][41][42][43][44].…”
Section: Machine Perfusionmentioning
confidence: 99%